(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Elderly population in Bangladesh is one of the largest in the world in term of absolute number and ageing is an emerging problem. Elderly are at risk from non-communicable diseases as well as mental problems and health-related quality of life (HRQoL) affects in urban and rural elderly. Objective: To find out and compare HRQoL in urban and rural elderly population of Bangladesh. Materials and Methods:A comparative cross-sectional study was carried out to compare HRQoL in urban and rural elderly. This was a two samples study; 130 each from urban and rural. Total 260 elderly were selected conveniently. Data were collected through face to face interview using a pre-tested semi structured questionnaire of SF-36 v2 HRQoL survey. This study was carried in urban elderly residing in Ward number 3, Race Course, Cumilla City Corporation and in rural elderly residing in Noapuskuni Village of Babutipara Union, Muradnager Upazila, Cumilla. This one-year study was conducted from 15 July 2017 to 14 June 2018. Results: Majority of the elderly were Muslim (91.5%), female (53.5%), married (59.6%) and from joint family (91%). The mean ± SD age of elderly was 69.26±6.337 years and mean ± SD monthly family income was Tk. 16561.54±9192.076. SF- 36 v2 HRQoL scale; a licensed software-based survey tool was used measure the health-related quality of life of elderly. Most of the elderly were found with average physical component summary (PCS) (53.1%) and mental component summary (MCS) (50.8%) of HRQoL. Age had significant negative correlation with PCS (p<0.001) and MCS (p<0.001) in urban and rural elderly. Education level of urban and rural elderly had significant positive correlation with PCS (p<0.01) and MCS (p<0.01). Marital status of urban and rural elderly had significant negative correlation with PCS (p<0.001) and MCS (p<0.001) of HRQoL. Among the rural respondents, the mean ± SD of PCS of male was 43.79±5.766 and female was 41.14±6.860. The difference was statistically significant (p<0.05). Mean score of PCS of urban and rural respondents were 45.68±6.366 and 42.43±6.467 respectively. This difference was statistically significant (p<0.001). Mean scores of MCS of urban and rural respondents were 43.96±4.921 and 42.56±7.028 respectively. This difference was not statistically significant (p>0.05). Conclusion: Most of the elderly had average level of health-related quality life. Rural female elderly had significantly lower physical health of HRQoL than that of rural male elderly. Physical dimension of HRQoL of rural elderly was significantly lower than that of urban elderly. JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 161-164